Implementasi Load Balancing untuk Kontroler Software Defined Network - Adi Iman Utama; Widhi Yahya; Dany Primanita Kartikasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The development of increasingly complex needs of traditional networks will affect the high cost of investment and hardware maintenance so that required solutions to these developments by using Software Defined Network (SDN). SDN is a concept of separation between control plane and data plane on network devices such as routers and switches, whereas in traditional networks the control plane and data plane are combined into one. Using a single controller on the SDN concept obtained a latency value with an average of 1000 to 1900 responses / second and throughput with an average of 50 to 300 flow / second, the value decreased performance when the number of switches connected in the network environment increased. In this research apply load balancing to do the load sharing on some controller that connected so that performance of each controller can run with maximal. The controller used in this research is POX while to implement load balancing controller will be used HAproxy on server computer. The test results show that as the increasing number of controllers with load balancing will provide better latency and throughput results from the use of 3 controllers obtained the latency value with an average of 2000 to 3300 responses / second and throughput with an average of 70 to 4300 flow / second, but as the number of controllers increases load of server load balancing will increase seen from CPU and Memory Usage.